Individual differences in the reproduction of temporal intervals - Du Preez, Peter Derek (Department of Psychology, 2016)
MAIN AIMS: (i) To determine the reliability of the reproduction of short time intervals by the method of linear arm movement under conditions of free movement (in which the distance and speed of the linear movement was left to the subject's own preference) and controlled movement (in which the distance, and, indirectly, the speed of linear movement was experimentally varied) (Chapter 4). (ii) To investigate relations among time judgements by different methods of reproduction and by verbal estimation (Chapter 5). (iii) To investigate motor time-space relations under conditions of free movement (Chapter 6) and controlled linear arm movement (Chapter 7). (iv) To investigate the effects of short periods of delay on the reproduction of short time intervals (Chapter 8). (v) To investigate the relationship between individual differences in extraversion (measured by the Maudsley Personality Inventory) and individual differences in the reproduction of short time intervals by both free and controlled linear arm movement (Chapter 9). (vi) To investigate the relationship between individual differences in measures of unstructured motor speed, measures of secondary functioning, and reproduction of short time intervals by free linear arm movements (Chapter 10). (vii) To investigate the relationship between individual differences in Taylor Manifest Anxiety score and individual differences in the reproduction of short time intervals by both free and controlled linear arm movement (Chapter 11). (viii) To investigate the relationship between individual differences in time imagery (measured by the Metaphor Preference Scale) and individual differences in the reproduction of short time intervals by both free and controlled linear arm movements (Chapter 12). (ix) To investigate the relationship between individual differences in n Achievement and individual differences in the reproduction of short time intervals by free linear arm movements (Chapter 12).